2020
DOI: 10.1108/ijqrm-04-2019-0131
|View full text |Cite
|
Sign up to set email alerts
|

Designing predictive maintenance systems using decision tree-based machine learning techniques

Abstract: PurposeThe after-sale service industry is estimated to contribute over 8 percent to the US GDP. For use in this considerably large service management industry, this article provides verification in the application of decision tree-based machine learning algorithms for optimal maintenance decision-making. The motivation for this research arose from discussions held with a large agricultural equipment manufacturing company interested in increasing the uptime of their expensive machinery and in helping their deal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 51 publications
0
43
1
Order By: Relevance
“…Some authors [10,30,[46][47][48][75][76][77]107,114,[118][119][120][121] focused on ANN ML algorithms. Some other authors [64][65][66][67]81,82,[84][85][86][87][88]90,116,117] studied RF technique. In the last years, use of SVM technique has received attention from authors [14,21,48,56,66,79,[93][94][95][96][97][98][99][100]102,107,111,115,121,124].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors [10,30,[46][47][48][75][76][77]107,114,[118][119][120][121] focused on ANN ML algorithms. Some other authors [64][65][66][67]81,82,[84][85][86][87][88]90,116,117] studied RF technique. In the last years, use of SVM technique has received attention from authors [14,21,48,56,66,79,[93][94][95][96][97][98][99][100]102,107,111,115,121,124].…”
mentioning
confidence: 99%
“…Some authors [21,56,82,112,120,124] have given attention to GBM technique. Some authors [65,66,79,109,112,117] carried out studies by use of DT technique. However, it is observed that there is less consideration given to XGBoost technique and there are only a few studies found in the literature [62,81,120].…”
mentioning
confidence: 99%
“…These sensor readings can determine the health of the equipment. As a result, there is a growing demand in the industry to perform maintenance on equipment based on their condition instead of the existing industry standard of time-based maintenance [33,34]. It has also been demonstrated that condition-based maintenance may save a lot of financial losses.…”
Section: Background and Related Workmentioning
confidence: 99%
“…All these revolutions considerably triggered the growth of manufacturing industry. In recent years, development of technologies like cyber physical system (CPS), AR and Internet of things (IoT) began a new revolution in Industries which was titled as Industry 4.0 (referred to as I4.0) in Hannover Fair in 2011 (Xu et al, 2018;Kaparthi and Bumblauskas, 2020). The understanding of big data analytics in Industry 4.0 workforce increases competitiveness among organization and thus differentiating the top companies from others (Navas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%